Tracking technical refinement in elite performers: The good, the better, and the ugly - Carson, H. J.; Collins, D. (International Journal of Golf Science, 2015)
This study extends coaching research examining the practical implementation of technical refinement in elite-level golfers. In doing so, we provide an initial check of precepts pertaining to the Five-A Model and, examine the dynamics between coaching, psychomotor, biomechanical, and psychological inputs to the process. Three case studies of golfers attempting refinements to their already well-established techniques are reported. Kinematic data were supplemented with intraindividual movement variability and self-perceptions of mental effort as measures of tracking behavior and motor control. Results showed different levels of success in refining technique and subsequent ability to return to executing under largely subconscious control. In one case, the technique was refined as intended but without consistent reduction of conscious attention, in another, both were successfully apparent, whereas in the third case neither was achieved. Implications of these studies are discussed with reference to the process` interdisciplinary nature and importance of the initial and final stages. ABSTRACT FROM AUTHOR See discussions, stats, and author profiles for this publication at: https://www.researchgate.net/publication/287122258